Case report: Methylphenidate improved chronic pain in an adult patient with attention deficit hyperactivity disorder - Zain, Ekachaeryanti; Sugimoto, Atsunori; Egawa, Jun; Someya, Toshiyuki (Frontiers in Psychiatry, 2023)
Introduction: Chronic pain remains a health problem that is difficult to treat adequately. Its unknown cause and complex comorbidity with other illnesses, including mental disorders, amplify the severity of symptoms, which consequently decreases the quality of life of patients long term. In our clinical practice, we coincidentally found evidence that methylphenidate (MPH) effectively managed chronic pain in an adult patient with attention deficit hyperactivity disorder (ADHD). The effectiveness of MPH in the treatment of ADHD is well-established; however, its utility in treating pain remains unclear. Case presentation: We present a rare case of a 43-year-old male patient with 15 years of chronic idiopathic pain symptoms that did not adequately respond to standard pain management, such as acetaminophen, non-opioid analgesics, and muscle relaxers. Pain also persisted after treatments with antidepressants and an epidural block. Furthermore, symptoms worsened following several sessions of modified electroconvulsive therapy. After a thorough assessment at our child and adolescent psychiatric outpatient clinic, we confirmed a diagnosis of adult ADHD with a predominantly inattentive type. Considering this newly established diagnosis, we prescribed osmotic-release oral system (OROS) methylphenidate. Within 1 month of treatment at a dose of 18 mg/day of OROS-MPH, the patient’s chronic pain unexpectedly improved dramatically, and the patient no longer experienced pain symptoms. The dosage of OROS-MPH was titrated monthly, reaching 72 mg/day as a maintenance dose, and ADHD symptoms improved after 4 months of treatment. The patient was followed up regularly for 7 years during his OROS-MPH treatment. No adverse effects were reported, including stimulant addiction. He was stable overall and functioned well in his daily activities. His pain never recurred. Conclusion: This case report suggests that MPH may be potentially effective in treating chronic pain. Further studies are needed to confirm whether MPH improved chronic pain simultaneously with or separately from the improvement in ADHD. Moreover, elucidating the anatomical sites and molecular pharmacological mechanisms related to the action of MPH in pain modulation and perception is essential. Such sites include the descending dopaminergic pain pathway and higher cortical areas. Furthering our understanding may reinforce the justification for treating chronic pain using MPH.